BIRGing with the Best; CORFing for the Country: Fan Identification and Nationalism during the 2014 FIFA World Cup. Issue 1 (2nd April 2016) - Billings, Andrew C.; Devlin, Michael B.; Brown, Kenon A.
ABSTRACT: To determine how consumption team performance (winning/losing) affects fan identification and subsequent nationalism traits, a national survey of 720 respondents was conducted at four different time periods throughout the 2014 FIFA World Cup. Using structural equation modelling, increased consumption significantly predicts fan identification towards the United States Men's National Team (USMNT). Consumption alone had no effect on nationalistic identity; however, fan identification towards USMNT significantly increased nationalised qualities one exhibits toward one's home country. Winning or losing had no effect on fan identity, yet losing did negatively affect fan internationalism scores and views of global citizenship. Ramifications are offered for theory as well as conclusions related to fan identity and nationalism as a byproduct from winning and losing.